COMMUNITY INVOLVEMENT IN THE WORLD OF EDUCATION - Rusnawati; Cut Puan Shabrina (Adisam Publisher, 2024)
Community involvement with educational institutions is a whole process of activities that are planned and carried out deliberately and seriously, accompanied by continuous training to gain sympathy from the community in general. Especially people who have a direct interest in education. Community sympathy will grow through the school's efforts to build relationships in an incentive and proactive manner in addition to building a good image of educational institutions. The quality of education is one of the indicators in determining the success of education. Improving the quality of education is closely related to the surrounding environment which includes community participation or involvement. In order to improve the quality of education, an active role from the community is needed to participate and be involved in educational programs or projects. It is very important to understand what forms of community involvement are appropriate to support the creation of improvements in the quality of education. Participation is the active involvement of a person or group of people (community) consciously to contribute voluntarily to development programs and involvement starting from planning, implementation, monitoring to the evaluation stage.